Family Influence on Female’s Blood Education in the Context of Islamic Practice in Malaysia - Tengku Kasim, Tengku Sarina Aini Binti; Yaakob, Siti Falihah Binti; Mohd Razif, Nor Fahimah Binti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Family is the first and foremost institution in the formation of an individual’s values, morals, and personality laying the foundation for societal harmony. A well-functioning family is capable of fostering a balanced and competitive society. In Islamic education, one crucial aspect that families need to emphasize is the education concerning women’s blood, encompassing topics such as menstruation, postpartum bleeding (nifas), irregular bleeding (istihadhah), and the related rulings. However, within the context of the Malaysian Muslim community, this topic is often underemphasized due to traditional perceptions that deem it unsuitable for open discussion. The lack of clear information has led to difficulties among young women in understanding the rulings related to women’s blood, potentially affecting the validity of their religious practices. This study investigates the extent to which Muslim families in Malaysia play a role in educating about women’s blood and examines how the lack of such education influences Islamic practices among Muslim women. Adopting a qualitative approach, the study employs semi-structured interviews and document analysis to explore family perspectives and experiences in conveying this knowledge. Findings indicate that families play a pivotal role in shaping attitudes, knowledge, and awareness among children, contributing to a deeper understanding of women’s blood-related topics. Abdullah Nasih Ulwan emphasized that parents are responsible for teaching their children the rulings of maturity, including those on menstruation and its associated laws.These findings suggest that integrated education on women’s blood should be prioritized within families and Islamic educational institutions to enhance family knowledge and well-being. The study also provides significant implications for policymakers and educators in designing more inclusive programs aligned with current religious and social needs.